2013
DOI: 10.1186/1757-2215-6-60
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing to GADPH jeopardises correct quantification of gene expression in ovarian tumours – IPO8 and RPL4 are reliable reference genes

Abstract: BackgroundTo ensure a correct interpretation of results obtained with quantitative real-time reverse transcription-polymerase chain reaction (RT-qPCR), it is critical to normalize to a reference gene with stable mRNA expression in the tissue of interest. GADPH is widely used as a reference gene in ovarian tumour studies, although lacking tissue-specific stability. The aim of this study was to identify alternative suitable reference genes for RT-qPCR studies on benign, borderline, and malignant ovarian tumours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Interestingly, this result is consistent with the findings of Kolkova et al, where ABL1 turned out to be the least stable gene found by NormFinder analysis in human ovarian tumor tissue. 56 The combined analysis of 2D and 3D cultivated BMMSCs with NormFinder again determined not only GAPDH, but also GADD45A and RPL37A as the least stable RGs. In contrast, the DNA-damage-inducible gene GADD45A was identified as the most stable RG in a previous investigation of our group in osteogenically induced BM-MSCs (32).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this result is consistent with the findings of Kolkova et al, where ABL1 turned out to be the least stable gene found by NormFinder analysis in human ovarian tumor tissue. 56 The combined analysis of 2D and 3D cultivated BMMSCs with NormFinder again determined not only GAPDH, but also GADD45A and RPL37A as the least stable RGs. In contrast, the DNA-damage-inducible gene GADD45A was identified as the most stable RG in a previous investigation of our group in osteogenically induced BM-MSCs (32).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, normalization is done using a single housekeeping gene [13]. However, several studies have revealed that these traditional reference genes are often not as stably expressed as expected, leading to misinterpretation of biological data [15,16]. Consequently, new and more stably expressed reference genes have been successfully identified in a variety of organisms [17], and the optimal reference genes were chosen to analyze the biological data accurately.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic activity of PPIA may affect its stability as a reference gene. ACTB (actin, beta) is related to cell motility, structure, and integrity; it is a structural protein [16] and has good stability, likely because outside conditions do not generally affect cell structure. To track small changes in gene expression, use of single internal genes often does not produce accurate quantitative results, so two or more internal genes should be used for reference calibration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression was assessed with Real-Time PCR using the TaqMan Gene Expression Assays (Applied Biosystems) for HMGA2 (Hs_04397751_m1), FHIT (Hs_00179987_m1), LIN28A (Hs_00702808_s1), and LIN28B (Hs_01013729_m1), whereas RPL4 (Hs_01939407_gH) was used as a reference gene as it has been proven to be stably expressed in ovarian cells [31, 32]. …”
Section: Methodsmentioning
confidence: 99%